Filling out the gaps – identification of fugralins as products of the PKS2 cluster in Fusarium graminearum - Severinsen, Manja Mølgaard; Westphal, Klaus Ringsborg; Terp, Mikael; Sørensen, Trine; Olsen, Anders; Bachleitner, Simone; Studt-Reinhold, Lena; Wimmer, Reinhard; Sondergaard, Teis Esben; Sørensen, Jens Laurids (Frontiers in Fungal Biology, 2023)
As one of the grain crop pathogenic fungi with the greatest impacts on agricultural economical as well as human health, an elaborate understanding of the life cycle and subsequent metabolome of Fusarium graminearum is of great interest. Throughout the lifetime of the fungus, it is known to produce a wide array of secondary metabolites, including polyketides. One of the F. graminearum polyketides which has remained a mystery until now has been elucidated in this work. Previously, it was suggested that the biosynthetic product of the PKS2 gene cluster was involved in active mycelial growth, the exact mechanism, however, remained unclear. In our work, disruption and overexpression of the PKS2 gene in F. graminearum enabled structural elucidation of a linear and a cyclic tetraketide with a double methyl group, named fugralin A and B, respectively. Further functional characterization showed that the compounds are not produced during infection, and that deletion and overexpression did not affect pathogenicity or visual growth. The compounds were shown to be volatile, which could point to possible functions that can be investigated further in future studies.